Akuisisi Data dan Kalibrasi pada Sistem Can Satellite (Cansat) - Wicaksono, Muhammad Jaka Wimbang; Lubis, Eka Mutia; Oktani, Dessy; Kamarudin, Kamarudin; Darmoyono, Aditya Gautama; Mahdaliza, Rahmi; Gusnam, Mu’thiana; Syafi’i, Ahmad; Diputra, Muhammad Naufal Airlangga; Nugraha, Danu Satia; Abrajano, Muhamad Shafiq; Syahputra, Rezza Eka (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2025)
This study aims to develop and test a data acquisition and calibration system for CanSat, a small nanosatellite designed as a cost-effective solution for collecting geographical and spatial data. CanSat collects data using BME-280, MPU-9250, and NEO-6M sensors, then transmits it via XBee to a GUI for controlling the release of the Heat Shield, parachute, and legs. The data is analyzed using statistical methods and transmitted via XBee S2C. The results show that the BME-280 has a standard error of 0.35 and a deviation of 0.77 for temperature, and a standard error of 0.06 with a deviation of 0.13 for air pressure. The altitude measurement has a standard error of 0.02 and a deviation of 0.05. Meanwhile, MPU-9250 has an average standard error of 0.34 and a deviation of 0.77 for angle orientation measurement. The design and testing of the leg control system conclude that it functions at 80% efficiency.